The role of the radiation therapy breast boost in the 2020s - M. Dzhugashvili; L. Veldeman; A.M. Kirby (Breast, 2023)
Given that most local relapses of breast cancer occur proximal to the original location of the primary, the delivery of additional radiation dose to breast tissue that contained the original primary cancer (known as a “boost”) has been a standard of care for some decades. In the context of falling relapse rates, however, it is an appropriate time to re-evaluate the role of the boost. This article reviews the evolution of the radiotherapy boost in breast cancer, discussing who to boost and how to boost in the 2020s, and arguing that, in both cases, less is more.